Seaweeds’ nutraceutical and biomedical potential in cancer therapy: a concise review - Cotas, João (2021)
Seaweeds have been a food source since ancient times (600 BC) and are still widely used in Asia, mainly in traditional Chinese medicine and Japanese folk medicine. Nowadays, seaweed compounds and extracts have been gaining interest from the biomedical and pharmaceutical market sectors. Seaweeds have been referenced as feasible solutions in finding new potential compounds and therapies in prevention, control, and reduction of cancer development due to the multirole of some bioactive components (e.g, phenolic compounds and sulphated polysaccharides). Moreover, seaweeds are rich in important health-promoting molecules [such as poly and highly unsaturated fatty acids (PUFAs and HUFAs), essential amino acids, vitamins, and dietary fibers] and minerals (calcium, iron, iodine, magnesium, phosphorus, potassium, zinc, copper, manganese, selenium, and fluoride). In this review, the potential therapeutic effects of seaweed in the prevention and treatment of cancer are approached, as well as nutraceutical properties of seaweed to promote cell homeostasis.